BOQ and BOM in the road management of Ukraine - Tsyfra Т. (Ways to Improve Construction Efficiency, 2023)
The article highlights theoretical and practical approaches to the use of BOQ and BOM forms in the road industry of Ukraine. Both BOQ and BOM are used to determine the quantity and specification of materials. A BOQ is specific to construction projects and focuses on estimating costs, while a BOM specification is also used in manufacturing and focuses on specifying the materials and components required for construction. Understanding the road industry’s pricing system and transitioning to the use of a Bill of Quantities (BOQ) and Bill of Materials (BOM) is vital to effective project management in both the construction and manufacturing sectors. While the BOQ mainly focuses on the quantification and costing of materials and labor, the BOM emphasizes the components required to produce the building materials as a product. BOQs focus on items, measurements, quantities, pricing, and cost breakdowns specific to construction projects, while BOMs emphasize components, specifications, descriptions, and hierarchical organization related to the production of road materials and the manufacturing environment. By using these two vital documents, you can streamline the business processes of project planning, procurement, and execution, leading to increased efficiency and successful project outcomes. By integrating BOM and BOQ into a single digital environment with financial ERP tools, businesses can gain real-time insight into project costs. It helps in budgeting, forecasting and ensuring the financial viability of the project and making operational changes to the 4d-5d BIM model. BIM can improve the accuracy and efficiency of both Bill of Quantities (BOQ) and Bill of Materials (BOM) by providing a more detailed and comprehensive set of data, providing a detailed and accurate representation of the project. BIM can also help identify potential clashes or conflicts between different components that can be resolved before construction begins. In addition, BIM can facilitate collaboration between the various stakeholders involved in a project.